Social Construction of Local Wisdom of Kaombo Laut in Binongko Island Communities, Wakatobi Islands - Turasih, Turasih (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
The people of Binongko Island are a community united by the customary rules of Sarano Wali as a traditional institution which is still maintained today. Sarano Wali's customary rules cover setting the values ​​of everyday life as well as managing interactions between humans and nature both on land and at sea. In the interaction between humans and marine resources on local wisdom values ​​called kaombo laut which contains the obligations and rights of the community towards marine resources and the sanctions in case of violations. This study aims to explore related: (1) marine kaombo as a form of local wisdom in regulating interactions between humans and marine resources on Binongko Island; and (2) the formation of marine kaombo social construction in the Binongko Island community. This research uses a qualitative approach with a case study method. Based on the results of the study it is known that sea kaombo is a form of regulation of opening and closing areas called toomboemo (closed) and bukaano kaombo (open). The sea kaombo procession uses traditional rituals carried out by the community through the Sarano Wali traditional institution. The social construction of marine kaombo in the Binongko Island community is realized from the continuous application of marine kaombo as a form of preserving local wisdom. Keywords: Social Construction, Kaombo, Local Wisdom, Sarano Wali, Wakatobi